2020
DOI: 10.1007/s11897-020-00474-y
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Cardiac Conduction System Pacing as a Treatment for Heart Failure

Abstract: Purpose of Review The aim of cardiac resynchronization therapy (CRT) is to improve cardiac function by delivering more physiological cardiac activation to patients with heart failure and conduction abnormalities. Biventricular pacing (BVP) is the most commonly used method for delivering CRT; it has been shown in large randomized controlled trials to significantly improve morbidity and mortality in patients with heart failure. However, BVP delivers only modest reductions in ventricular activation time and is on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…poor improvement in NYHA class, QRS duration, or echocardiographic parameters) [64]. Furthermore, while conventional CRT does improve QRS duration, it does not return it to a range seen in patients with intact conduction tissue, suggesting better therapeutic benefits with shorter QRS [65]. Whether CSP can be used as an alternative to, or as rescue therapy for patients with an indication for CRT remains to be seen.…”
Section: Conductive System Pacingmentioning
confidence: 99%
“…poor improvement in NYHA class, QRS duration, or echocardiographic parameters) [64]. Furthermore, while conventional CRT does improve QRS duration, it does not return it to a range seen in patients with intact conduction tissue, suggesting better therapeutic benefits with shorter QRS [65]. Whether CSP can be used as an alternative to, or as rescue therapy for patients with an indication for CRT remains to be seen.…”
Section: Conductive System Pacingmentioning
confidence: 99%
“…Experiments have shown that CSP is an important alternative in solving the residual dyssynchrony problem created by conventional BVP between the 2 ventricles and in the interventricular septum ( Table 2 ). 23 In addition, considering that IVCD is not limited to the distal area and may include the proximal conduction system in patients with poor conventional CRT response, it is thought that CSP can be used as the first choice in appropriate patient groups 24 ( Figures 2 and 3 ).…”
Section: Current Clinical Practice In Crt Implantationmentioning
confidence: 99%
“…It is clearly so that more accurate knowledge is better, but at the same time it is certainly also true that the society of anatomical sciences has an epigenetic state predisposing it to spending many words on fine details. The cardiac conduction system, however, exemplifies a case where painstaking and tedious anatomical work led to insights of great clinical importance such as which parts of the heart can be operated on in corrective surgery [ 117 , 118 , 119 ] and which parts are most suitable for artificial pacing [ 120 , 121 ].…”
Section: The Special Case Of the Cardiac Conduction Systemmentioning
confidence: 99%